Données concernant la floraison des eaux du littoral roumain de la Mer Noire avec le péridinien exuviaella cordata ostf. - Bodeanu, Nicolae; Roban, Anca (Cercetări Marine - Recherches Marines, 2026)
This paper concerns the Exuviaella cordata ’’blooming" during the summer of the years 1974 and 1975, in the waters of the Black Sea along the Romanian shores. There are analyzed the factors concurrent to the apparition of this phenomenon, its immediate effects, including the mass mortality of marine animals which occurred.